INOVASI PEMBELAJARAN BAHASA INGGRIS MELALUI MEDIA FLASHCARD DI MADRASAH IBTIDAIYAH - Bisaroh, Zakiatul; Faruq, Dukan Jauhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
English language learning at the elementary education level, particularly in Madrasah Ibtidaiyah, plays an important role in developing students’ basic language skills from an early age. However, vocabulary learning in lower grades is still commonly conducted using conventional methods such as textbooks and memorization, which often result in low student participation and boredom. Therefore, learning innovations are needed to create more engaging, concrete, and meaningful learning experiences.This study aims to describe the innovation of English language learning through the use of flashcard media in Grade II of Madrasah Ibtidaiyah Unggulan Bustanul Ma’arif. Specifically, the study seeks to describe the implementation process of flashcards, students’ responses and learning activeness during the learning process, and changes in students’ English vocabulary mastery after the use of flashcard media.This research employed a qualitative approach with a descriptive research design. The research subjects consisted of an English teacher and second-grade students. Data were collected through classroom observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The results indicate that the use of flashcard media was implemented in a structured manner through vocabulary introduction using illustrated flashcards, joint pronunciation practice, and interactive exercises. The flashcard media increased students’ learning activeness and enthusiasm and had a positive impact on improving students’ English vocabulary mastery.